915 Evaluating the implementation of a sport injury prevention program in a school setting. (1st September 2016) - Richmond, Sarah A; Owoeye, Oluwatoyosi; Nettel-Aguirre, Alberto; Macpherson, Alison; Berg, Carla van den; Hagel, Brent; Verhagen, Evert; Finch, Caroline; Emery, Carolyn
Abstract : Background: Sport injuries are a significant burden, and while there are studies demonstrating the effectiveness of injury prevention programs, there is less guidance on how they are adopted and implemented successfully. The aim of this project was to conduct a process and formative evaluation of an injury prevention program implemented in a school setting. Methods: This study proposes two frameworks [RE-AIM and the Consolidated Framework for Implementation Research (CFIR)] to evaluate the implementation of a neuromuscular training program (iSPRINT) to reduce sport injury and improve health-related measures in a junior high school population. The five dimensions of the RE-AIM and CIFR frameworks will be used. Results: A total of 245/320 students were willing to participate in the program (68% reach). There was a lower risk of injury in intervention schools (n = 2) compared to controls (n = 2) [RR = 0.52 (95% CI: 0.33–0.81)]. 76% of students and 83% of teachers reported positive attitudes towards the program, 60% of students reported they believed the program could reduce the risk of injury, and 74% reported the program could improve fitness. 14% of the schools approached agreed to participate in the program (adoption). For students, the most frequently reported reason for participating was the belief that the program would reduce injury and increase fitness. Factors related to successful implementation of the program in schools included clear explanation and demonstration of the program, and barriers included difficulty in executing certain program components. Finally, 88% of teachers reported interest in maintaining the program. Ongoing formative evaluation will be collected via focus groups using CFIR constructs (2015–2016). Conclusions: Teachers were able and keen to continue to use the iSPRINT program. We will provide further discussion on the dimensions of REAIM, and report the specific constructs that facilitated and impeded implementation of the iSPRINT program.